The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fphar.2021.678713
|View full text |Cite
|
Sign up to set email alerts
|

Angelica Dahurica Regulated the Polarization of Macrophages and Accelerated Wound Healing in Diabetes: A Network Pharmacology Study and In Vivo Experimental Validation

Abstract: Diabetic wounds exhibit retarded and partial healing processes. Therefore, patients are exposed to an elevated risk of infection. It has been verified that Angelica dahurica (Hoffm.) Benth. and Hook. f. ex Franch. and Sav (A. dahurica) is conducive for wound healing. However, the pharmacological mechanisms of A. dahurica are yet to be established. The present study uses network pharmacology and in vivo experimental validation to investigate the underlying process that makes A. dahurica conducive for faster wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Angiogenesis is a pivotal process in wound repair, and this therapeutic property of A. dahurica root makes its use relevant for wound healing. The oral intake of A. dahurica also regulates the polarization of M1 and M2 subtypes of macrophages and thus inflammation ( Hu et al, 2021 ). On the diabetic mice model, oral intake of the A. dahurica root extract activated the phosphoinositide 3-kinase/protein kinase B signaling pathway (PI3K/AKT).…”
Section: Wound-healing Herbal Topical Therapies From Kampomentioning
confidence: 99%
“…Angiogenesis is a pivotal process in wound repair, and this therapeutic property of A. dahurica root makes its use relevant for wound healing. The oral intake of A. dahurica also regulates the polarization of M1 and M2 subtypes of macrophages and thus inflammation ( Hu et al, 2021 ). On the diabetic mice model, oral intake of the A. dahurica root extract activated the phosphoinositide 3-kinase/protein kinase B signaling pathway (PI3K/AKT).…”
Section: Wound-healing Herbal Topical Therapies From Kampomentioning
confidence: 99%
“…dahurica was extensively used as a traditional Chinese medicine in treating skin-associated diseases. In recent years, several studies revealed that A. dahurica has excellent activity on diabetes-induced skin ulcer (Guo et al, 2020;Chao et al, 2021;Hu et al, 2021). Guo et al (2020) indicated that 10 days treatment with A. dahurica at 1.8 g/kg b. w. significantly promoted would healing and angiogenesis by activating phosphatidylinositide 3kinase/protein kinase B (PI3K/AKT) and HIF-1α/plateletderived growth factor-β (PDGF-β) pathways in db/db mice.…”
Section: Effects On Skin Diseasesmentioning
confidence: 99%
“…Some of these bioactivities are consistent with the traditional uses of A. dahurica root, such as analgesic activity and effects on skin diseases. In addition, A. dahurica also exerts specific effects, related to anti-diabetic (Han et al, 2018), lowering blood lipids (Lu et al, 2016), improving immunity (Wang et al, 2021), anti-ulcer (Hu et al, 2021) and cosmetic effects (Cho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts are critical in the proliferation phase of wound healing and play a dominant role in collagen deposition, granulation tissue formation, and epithelialization ( Liu et al, 2022 ). Currently, various therapeutic approaches have been used in the treatment of chronic non-healing wounds, including surgical debridement, antimicrobial agents, bioengineered skin equivalents, and growth factors ( Han and Ceilley, 2017 ; Dubey et al, 2021 ; Hu et al, 2021 ; Sarojini et al, 2021 ; Wang et al, 2021 ). However, limited therapeutic effects and numerous side effects restrict their application ( Han and Ceilley, 2017 ).…”
Section: Introductionmentioning
confidence: 99%